The Development of Design and Manufacturing Process for Community Products under the Limitation of Elderly Potential - chantarasakha, kanyakorn; piajantuek, phannipha (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
This research aims to develop a variety of product design and manufacturing processes suitable for elders based on Isan local wisdom which are in the current social context and help increase the physical potential and ability of the elderly to do activities. This qualitative research collected data from informants, including elders, community developers, product development specialists and local product development and marketing specialists, by using in-depth interview and focus group discussion techniques, applying the analytical descriptive approach to analyze data by firstly considering major themes and dividing them into sub-themes then using the content synthesis technique to link process data. Research findings revealed that the elderly had to be active at all times, the elderly would be happy when choosing activities that require skilled craftsmanship and are achievable. The elderly selected skill-based activities, which they had skills and aptitudes, and emphasized on rehabilitated the elderly’s previous knowledge. Reviewing previous experiences and commenting while working on an activity, and cognitive ability of the elderly could lead to potential development while doing activities. Guidelines for product development and manufacturing which are appropriate for elders from this research were bringing their own products to ask experts for analysis and find ways to develop, enhancing a product to have distinctive differences, branding to gain acceptance and have a story. That product would be able to raise the identity of local wisdom with valuable stories which could be regarded as the cultural capital which can be used to create designs.